How does 11-week detraining affect 11-12 years old swimmers` biomechanical determinants and its relationship with 100 m freestyle performance? - Morais, J. E.; Lopes, V. P.; Barbosa, T. M.; Moriyama, S.-I.; Marinho, D. A. (Sports Biomechanics, 2022)
The aim of this study was to analyse the detraining process that occurs during a season break, and its influence on the performance, anthropometrics, and biomechanics of young swimmers. The sample included 54 young swimmers (22 boys: 12.79 ± 0.71 years; 32 girls: 11.78 ± 0.85 years). Performance for the 100 m freestyle and anthropometric and biomechanical variables were evaluated as main determinants. Performance impaired significantly for boys (2.17%) and girls (1.91%). All anthropometric variables increased between moments of assessment for boys and girls. Overall, the boys enhanced all biomechanical variables during the detraining period, and girls showed mixed results. For both sexes, the stroke index was the variable with the highest increase (boys: delta = 16.16%; d = 0.89; p = 0.001; girls: delta = 19.51%; d = 1.06; p = 0.002). Hierarchical linear modelling showed that the height retained the amount of impairment in the performance. One unit of increase in the height (cm) led to less 0.41 s impairment in the performance. Present data indicated that during an 11-weeks detraining period, young swimmers impaired their performance, but the determinant factors showed an impaired relationship. This increase in the determinant factors is mainly related to the increase in the swimmers` anthropometrics. Moreover, the increase in height was responsible for retaining the performance impairment.